The Effectiveness of PBL Model Physics e-Book with STEMI Approach to Improve Student’s Problem-Solving Ability in terms of Gender - Bahtiar Bahtiar; Muhammad Kafrawi (JIPF (Jurnal Ilmu Pendidikan Fisika), 2023)
The learning process that uses learning models and approaches that involve the active role of students can improve students' abilities. This study aims to analyze the effectiveness of the physics e-book PBL model with a STEMI approach to improve students’ problem-solving abilities in terms of gender. In this quantitative study, a one group pretest-posttest approach was used. The research sample used was 55 class XI students of MA Hidayatullah Mataram, of which 25 were male students and 30 were female students. Collecting data on the effectiveness of using the problem-solving ability description instrument which consists of eight questions. Effectiveness data analysis used the N-Gain test and Rash model analysis. The results showed that male students dominated the IPSA-1 indicator (89.06) and IPSA-2 (68.23), while female students were more dominant in the IPSA-3 (89.19), IPSA-4 (76.35), and IPSA-5 (71.35). The results also showed that female students in all sub-subjects of work and energy had a higher average score than male students. In general, the results of the study also show that the PBL model physics e-book with the STEMI approach used in the learning process is effective in increasing the PSA of male and female students with an N-Gain score of 70.04.